Ciclos anuais em aves de ambiente florestal: muda de penas e reprodução - Dantas, Thaís (2013)
Molting and reproduction are two important stages in the life of birds that require high energy demand, with no tendency to overlap. The objectives were: 1) describe the presence of molt, brood patches and subcutaneous fat of the birds in the forest, and there is overlap of molting and reproduction phases, 2) determine the period in which there is greater availability of resources (fruits and arthropods) and 3 ) relate the stages of molt and breeding the average monthly precipitation and 4) determine variations in diet during molting and reproduction through the fecal analysis. The study was conducted between July 2011 and November 2012, in a forest fragment present in the Fazenda Experimental do Glória. The birds were captured with the aid of mist nets. The molt was determined by the presence of cannons feathers, being differentiated molt in contour, symmetrical wing, symmetrical tail. Reproduction was assessed by the presence of brood pactches at different scales. The deposition of subcutaneous fat was estimated. The availability of arthropods and fruits was measured monthly. The average monthly rainfall data were provided by Laboratório de Climatologia e Recursos (UFU). We captured 553 individuals belonging to 39 species in 16 families. The most frequent was Antilophia galeata (34%, N = 186), followed by Basileuterus hypoleucus (13%, N = 72) and Arremon flavirostris (7%, N = 42). The default time for the molt was not determined due to low capture individuals who had cannon feathers. Reproduction concentrated in the months of August/October, and there was fat subcutaneous throughout the year. There was resource availability throughout the year, peaking in November and July arthropods to ripe fruit. The precipitation influenced the molt and did not affect reproduction. Antilophia galeata molting held in November and April, peaking in January. Reproduction occurred between April and October, peaking in July, there was a minimal overlap of the peaks of both phases. There was accumulation of fat throughout the year, but with a significant difference in June. The molt correlated with precipitation, which had no effect on reproduction. Antilophia galeata consumed fruits and arthropods during sampling from March. It is concluded that the stability of the environment, with food resources present throughout the year, allows one to decide when to make the molt and reproduction.